Ruling On Betting in Sports and Educational Competitions in Islamic jurisprudence - Zobair Nabi ahmed; Hussein Saad Eddin Masoud (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Praise be to God, and prayers and peace be upon the Messenger of God, as for what follows: The subject of the rule of betting in sports and educational competitions is one of the important topics that needs to be explained, especially in our time, which has increased widely, especially at the international level, and the jurists have agreed in the sentence on its permissibility; Some of them permitted some of them, and some of them permitted some types of them, and some of them permitted them absolutely. The scholars also differed regarding the conditions for permissibility of betting contracts, and the title of this research was named: (The Ruling on Betting in Sports and Educational Competitions). In this research, I referred to the definition of betting, which is: two or more people bet on an amount of money in a competition, and whoever wins takes money, and I have shown its types and forms. I explained the ruling on betting with mosquitoes in sports competitions of all kinds through the sayings of scholars and their evidence, so it became clear to me: that holding betting with mosquitoes in sports competitions that lead to strengthening the body, exercising the body and stretching the body so that the Muslim is ready to face any external danger, it is permissible. We talked about betting in educational competitions and religious discussions through the sayings and evidence of scholars, and it became clear to me: its permissibility, because of the manifestation of religion and its theoretical proofs in return for the construction of religion and the tightening of its governmental authority, which are two sides of the same coin. Then we explained the ruling on betting against the expectations of the results of sports competitions, as is the case today in the bets that are concluded between football fans on the prediction of the results of matches and between the companies sponsoring them. Result to show religion and its provisions. And Praise be to Allah, the Lord of the Worlds.